2018
DOI: 10.1097/iae.0000000000001645
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Central Choroidal Thickness After Treatment of Diabetic Macular Edema With Intravitreal Bevacizumab Correlation With Central Macular Thickness and Best-Corrected Visual Acuity

Abstract: After treatment of diabetic macular edema with intravitreal injection of bevacizumab, CCT decreased and this reduction significantly correlated with CMT reduction and vision improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
2
19
4
Order By: Relevance
“…Several studies also have shown that the SFChT decreased after intravitreal injection of anti-vascular endothelial growth factor (VEGF), which suggests that the choroid is sensitive to intraocular VEGF concentration. 19 , 20 The most important finding of the present study was the increase in the SFChT in eyes with treatment-naïve PDR, which had considerably high concentrations of VEGF. 21 , 22 The choroidal thickening in treatment-naïve PDR might reflect the increased concentration of VEGF or a large area of nonperfusion.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies also have shown that the SFChT decreased after intravitreal injection of anti-vascular endothelial growth factor (VEGF), which suggests that the choroid is sensitive to intraocular VEGF concentration. 19 , 20 The most important finding of the present study was the increase in the SFChT in eyes with treatment-naïve PDR, which had considerably high concentrations of VEGF. 21 , 22 The choroidal thickening in treatment-naïve PDR might reflect the increased concentration of VEGF or a large area of nonperfusion.…”
Section: Discussionmentioning
confidence: 51%
“…In DME patients, all studies have shown that anti-VEGF injections reduce the central CT, although the clinical consequences of this reduction remain unclear. Some studies have found an association between the decrease in the central CT and the decrease in CRT and the visual gain under anti-VEGF treatment [ 15 ]. Other studies have not been able to find such an association with the visual gain [ 9 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Campos et al [ 16 ] and Yiu et al [ 17 ] have suggested that the CSCT was not predictive of the anatomical or functional outcomes of DME. However, in a prospective study of 20 eyes of 20 treatment-naive DME patients, a decrease in the central CT 6 months after treatment with 3 IVI of bevacizumab has been shown, and this reduction significantly correlated with a reduction in CRT and with an improvement in visual acuity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported about the effect of PRP on ChT [ 20 ]. Moreover, several studies showed that ChT reduces after intravitreal injection of anti-VEGF [ 21 ]. Thus, we believed that it was essential to exclude eyes with treatment histories.…”
Section: Discussionmentioning
confidence: 99%